2018
DOI: 10.1091/mbc.e17-06-0364
|View full text |Cite
|
Sign up to set email alerts
|

In wound repair vimentin mediates the transition of mesenchymal leader cells to a myofibroblast phenotype

Abstract: Following injury, mesenchymal repair cells are activated to function as leader cells that modulate wound healing. These cells have the potential to differentiate to myofibroblasts, resulting in fibrosis and scarring. The signals underlying these differing pathways are complex and incompletely understood. The ex vivo mock cataract surgery cultures are an attractive model with which to address this question. With this model we study, concurrently, the mechanisms that control mesenchymal leader cell function in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 81 publications
5
104
0
Order By: Relevance
“…31,36 Vimentin is not only up-regulated in the cells but also excreted into the extracellular space. 37 The result of our studies suggest that the mechanical changes vimentin undergoes in this pH range are considerable and might play a role within cells as well as the extracellular space during skin repair. Intracellular and extracellular pH gradients have furthermore been found to be a feature of migrating tumor cells.…”
Section: If Stiffening Saturates At Low Phmentioning
confidence: 73%
“…31,36 Vimentin is not only up-regulated in the cells but also excreted into the extracellular space. 37 The result of our studies suggest that the mechanical changes vimentin undergoes in this pH range are considerable and might play a role within cells as well as the extracellular space during skin repair. Intracellular and extracellular pH gradients have furthermore been found to be a feature of migrating tumor cells.…”
Section: If Stiffening Saturates At Low Phmentioning
confidence: 73%
“…Due to the numerous roles of vimentin, the effect of vimentin inhibition in non-malignant cells should be considered. To this end, consequences of its inhibition should be studied in animal models and effects on processes entailing cell migration (such as wound healing [73,133] or immune response [87,134]) should be carefully examined. However, since mice lacking vimentin develop and reproduce without any major problem [135], we can anticipate that beneficial vimentin inhibition in malignant cells outweighs any potential adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin is an essential element of inflammation and fibrosis. Walker et al 40 showed that vimentin mediates the transition of mesenchymal leader cells to a myofibroblast phenotype, facilitating fibrosis in wound repair, while vimentin deficiency resulted in a blunted inflammatory response. Vimentin is also a key regulator of the NLRP3 inflammasome, promoting lung inflammation and fibrosis 13 .…”
Section: Discussionmentioning
confidence: 99%